Chronic Disease Health Knowledge: A Survey of Older Adults Living in Ontario Social Housing - Brar, Jasdeep; Dias, Hanna; Sadri, Pauneez; Keenan, Amelia; Pirrie, Melissa; Angeles, Ric; Marzanek, Francine; Koester, Christie; Plishka, Mikayla; Dzerounian, Jasmine; AlShenaiber, Leena; Agarwal, Gina (My University, 2022)
A cross-sectional survey with adults ages 55+ (n=599) from 16 social housing buildings across five Ontario communities used the Health Awareness and Behaviour Tool (HABiT) to measure participants' health knowledge of heart disease and diabetes.
Keywords: Health Knowledge; Primary Care; Vulnerable Populations; Social Housing